Fair Legal Protection for Geothermal Development Companies that Already Have Business Licenses - I Made Subagio (Ridwan Institute, 2023)
The objectives of this study are; 1) to know and analyze geothermal business licensing arrangements that have provided fair legal protection for geothermal development companies. 2) Knowing and analyzing the implementation of geothermal exploitation policies has provided fair legal certainty in protecting geothermal development companies. 3) To analyze and review the direction of equitable regulation to provide legal protection for geothermal development companies. This research is a mixed research method, namely normative juridical and empirical juridical. The type of research used in this study is qualitative research, which is research that can be interpreted as research that does not carry out calculations. Result of this research stated that Geothermal business licensing arrangements have provided fair legal protection for geothermal development companies. Regarding licensing, the legal basis or regulations related to licensing in the geothermal sector as stated in the interview results that the regulations consist of Law Number 21 of 2014 concerning Geothermal and Law Number 11 of 2020 concerning Job Creation, then there are PP No. 7 of 2017, PP No. 28 of 2016, PP No. 5 of 2021, and PP No. 26 of 2022.